Letter (copy) : Scottish Ambulance Unit - Capture of Mr. McMahon and Mr. Boyd in Madrid - McDonald, Florence
010-0046-001 FEM/KMS/132. Secretary's. Alderman Midgley, 19, Garfield Chambers, Royal Avenue, Belfast. Dear Mr. Midgley, SCOTTISH AMBULANCE UNIT - Capture of Mr. McMahon and Mr. Boyd in Madrid. Sir Walter is at present out of London making arrangements for our next Congress, but he asked me to send you further news of Mr. McMahon and Mr. Boyd as soon as it was received. The Foreign 0ffice have now informed Sir Walter that the Burgos authorities have informed the British Ambassador at Hendaye that Mr. McMahon and Mr. Boyd are being properly cared for, and will be placed at liberty at whatever point on the frontier that they may select. Your sincerely, Private Secretary. 292/946/10/49